Continuous solid-state phase transitions in energy storage materials with orientational disorder – Computational and experimental approach. (November 2015) - Singh, Harpreet; Talekar, Anjali; Chien, Wen-Ming; Shi, Renhai; Chandra, Dhanesh; Mishra, Amrita; Tirumala, Muralidhar; Nelson, Daryl J.
Abstract: We report on TES (thermal energy storage) in new CT (continuous phase transitions) in multicomponent tetrahederally configured (orientationally disordered) crystals of NPG-neopentylglycol-C5 H12 O2, PG-pentaglycerine-C5 H12 O3, and PE-pentaerythritol-C5 H12 O4 . This discovery is applicable in thermal energy storage in many systems which do not require conventional isothermal first-order phase transition energy storage. The above compounds exhibit polymorphs of orientationally disordered phases in which O–H…O bond rotation around the C–C bond stores significant amount of energy; for example, in PE 41.26 kJ/mol are absorbed isothermally during solid–solid transitions. In this paper we show, anisothermal continuous phase transitions (CT), due to compositional changes with changes in temperature, associated with a measurable amount of energy, not reported earlier. The correlation of phase stability regions in pseudo-binaries, calculated from ternary NPG–PG–PE phase diagrams, is validated by experimental ternary DSC (differential scanning calorimetry) and in-situ x-ray diffraction data. We established equations for determining the CT in a temperature range, and their respective enthalpies of transitions for any composition of the ternaries. Thermodynamic calculations of the Gibbs energies of the solution phases are modeled as substitutional solid solutions, in which the excess Gibbs energies are expressed by the Redlich–Kister–Muggianu polynomial. There is excellent agreement between the experimental and CALPHAD calculated data. Highlights: Continuous phase transition (CT) thermal energy storage in organic ternary system. Anisothermal temperature ramping leads to CT transitions as per lever rule. Orientationally disordered phases store energy in O–H…O bond rotation/oscillation. Validated calculated data with measured thermodynamic properties in ternary system. Used CALPHAD methodology to calculate Gibbs energies of the solution phases.